Pentingnya Mewujudkan Pertahanan dan Keamanan Bagi Generasi Z di Era Media Sosial - Amanda, Nauva; Veronica, Ester; Liandi, Vina Verensia; Simanjuntak, Rahel Rezky; Subakdi, Subakdi (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In the digital era, the spread of hoaxes poses a serious threat to national defense and security. False and misleading information can easily spread through social media, causing unrest in society and even disrupting the stability of the country. Generation Z, as active users of social media, is vulnerable to being exposed to hoaxes and is the main target for spreading them. This research aims to socialize the importance of digital literacy and strategies for dealing with hoaxes to Generation Z at SMAN 108 Jakarta. By increasing their understanding and skills in analyzing and verifying information, it is hoped that Generation Z can become the country's defense in the digital era. This research uses a descriptive qualitative method with a case study approach. Data was collected through interviews, observations and surveys of representatives of Generation Z students at SMAN 108 Jakarta. The research results show that Generation Z has sufficient understanding of digital literacy and hoaxes. They also have sufficient skills to analyze and verify information. The dissemination of digital literacy and strategies for dealing with hoaxes has proven to be effective in comprehensive information about SMAN 108 Jakarta students' understanding of the spread of hoaxes in the digital sphere. After participating in the socialization, they showed an increase in students' understanding of SMAN 108 Jakarta in using technology as wisely as possible, as well as how to deal with the spread of fake news on social media from the socialization activities that would be carried out. This research shows that disseminating digital literacy and strategies for dealing with hoaxes are important for improving national defense and security in the digital era. Generation Z needs to become smart and responsible netizens to combat the spread of hoaxes. With adequate understanding and skills, they can become agents of change and contribute to the creation of a safe and conducive digital society. It is hoped that this socialization can provide a deep understanding of the importance of handling hoaxes that spread in the digital space and become the basis for an education project for young students at SMAN 108 Jakarta as Generation Z, thereby giving birth to a generation that can think critically. With joint efforts, we can realize stronger national defense and security in the digital era.